Visual Perception Evaluation Of Corten Steel: ŞImal Shopping Mall - İSMAİLOĞLU Semiha; AKKAN ÇAVDAR Ayça (Architecture, Civil Engineering, Environment)
Corten steel, or the corrosion of steel, is a result of exposure to the atmosphere. Corten steel is a recyclable, energy efficient, durable, and aesthetic material in terms of sustainability. This study aims to challenge the negative perceptions of Corten steel in society, stemming from its color and texture characteristics; and emphasize its importance in terms of sustainability and to prevent the prejudice of society. The purpose of the study is to determine the perceptions and satisfaction levels of Şimal AVM users towards Corten steel used as façade material. It is expected that the work will have an awareness-raising effect on the Corten steel material, which can create a perception of “deterioration” and “rusty”. The sample of the study consists of 221 users who have experienced Şimal AVM at least once. Additionally, a meeting was held with the architects of the building on the subject. As a result, Corten steel has a negative perception among users, primarily comprising negative (rusty, dirty, unhealthy etc) perceptions in physical, environmental, and emotional terms. However, after the study, it was determined that there were users whose perspective on the material changed.